2005
DOI: 10.1093/rpd/nci300
|View full text |Cite
|
Sign up to set email alerts
|

Occupational radiation exposure to norms in a gold mine

Abstract: Preliminary studies have been conducted into the occupational radiation exposure to NORMS from surface and underground mining operations in a gold mine in the Ashanti Region of Ghana. A brief description of the methods and instrumentation is presented. The annual effective dose has been estimated to be 0.26 +/- 0.11 mSv for surface mining and 1.83 +/- 0.56 mSv for the underground mines using the ICRP dose calculation method. The results obtained are found to be within the allowable limit of 20 mSv per annum fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…A recent study of Ghana found mean radon activities in underground gold mines of 350-445 Bq/m 3 , leading to exposures of about 1.83 mSv/year (mining only) (Darko et al 2005). Surface outdoor radon activities ranged from 24 to 41 Bq/m 3 in the mill, tailings dams, stockpiles and shafts/declines, leading to exposures of about 0.13-0.17 mSv/year.…”
Section: Gold Mining and Millingmentioning
confidence: 99%
“…A recent study of Ghana found mean radon activities in underground gold mines of 350-445 Bq/m 3 , leading to exposures of about 1.83 mSv/year (mining only) (Darko et al 2005). Surface outdoor radon activities ranged from 24 to 41 Bq/m 3 in the mill, tailings dams, stockpiles and shafts/declines, leading to exposures of about 0.13-0.17 mSv/year.…”
Section: Gold Mining and Millingmentioning
confidence: 99%
“…Radionuclide concentrations resulting from industrial activities such as mining and mineral processing has not been evaluated in almost all the mines in Ghana. Data on radionuclide concentrations in raw materials, mine tailings, scales in pipes, waste streams and public exposures in Ghana are scanty (Darko et al 2005;Darko and Faanu 2007). Consequently, there is general lack of awareness and knowledge of the radiological hazards and exposure levels by legislators, regulators and operators.…”
Section: Introductionmentioning
confidence: 99%
“…The method of the γ-ray analysis reported in published research works 37 , 38 was adopted for this study. The gamma spectrometer used for the analysis consists of an ORTEC GEM Coaxial n-type HPGe gamma-ray detector with ORTEC Multichannel Analyzer (MCA) and MAESTRO-32 evaluation software for spectrum acquisition and processing.…”
Section: Methodsmentioning
confidence: 99%
“…The activity concentrations of 238 U, 232 Th and 40 K were determined in the soil and water samples were calculated using the following analytical expression as shown in equation 37 , 39 , 40 . where;…”
Section: Methodsmentioning
confidence: 99%